Cerebral phaeohyphomycosis due to Rhinocladiella mackenziei (formerly Ramichloridium mackenziei): Case presentation and literature review - Jaffar A. Al-Tawfiq; Ali Boukhamseen (Elsevier, 2011)
Summary: Rhinocladiella mackenziei (formerly Ramichloridium mackenziei), a causative agent of cerebral phaeohyphomycosis, is extremely rare and it is geographically limited to the Middle East. The organism has a predilection to cause brain infections and results in a grave prognosis with a high mortality rate. The current patient was admitted to a long term care facility with chronic respiratory failure and dependence on a mechanical ventilator. She later developed left sided weakness and a CT-scan of the brain revealed multiple variable sized hypodense, well-defined lesions with ring enhancement. A stereotactic needle aspiration of the largest lesion showed fungal hyphae. The final culture grew R. mackenzie. The patient was initially started on liposomal amphotericin B, then voriconazole and caspofungin intravenously as posaconazole was not available. The patient failed to respond to antifungal therapy and finally she died 34 days after the start of the treatment. R. mackenziei is a highly virulent agent, and should be considered in the differential diagnosis of central nervous system disease in patients from the Middle East. Keywords: Phaeohyphomycosis, Rhinocladiella mackenziei, Ramichloridium mackenziei